Pengaruh Struktur Modal Terhadap Profitabilitas Perusahaan Sektor Perbankan - Nabilla (Jurnal Ilmu Manajemen dan Akuntansi Nusantara, 2025)
This study aims to analyze the effect of capital structure on the profitability of banking sector companies listed on the Indonesia Stock Exchange. Using a quantitative approach and purposive sampling method, panel data from annual financial reports were analyzed using a panel data regression model. Capital structure is proxied by the Debt to Equity Ratio (DER), while profitability is measured by Return on Assets (ROA). The research findings reveal that capital structure has a significant negative effect on profitability. This indicates that the higher a bank's debt level, its profitability tends to decrease. This result supports the arguments of the Pecking Order Theory, where more profitable firms tend to rely on internal financing, thus having lower debt ratios. The implication of this study is the importance for banking management to maintain a strong capital structure to improve financial performance and ensure long-term stability.